2018
DOI: 10.1002/jbt.22206
|View full text |Cite|
|
Sign up to set email alerts
|

[6]‐Gingerol–induced cell cycle arrest, reactive oxygen species generation, and disruption of mitochondrial membrane potential are associated with apoptosis in human gastric cancer (AGS) cells

Abstract: Ginger (Zingiber officinale Roscoe), a monocotyledonous herb, is widely used as an herbal medicine owing to the phytoconstituents it possesses. In the current study, the quantity of [6]-gingerol, the major phenolic ketone, in the fresh ginger and dried ginger rhizome was found to be 6.11 µg/mg and 0.407 µg/mg. Furthermore, [6]-gingerol was assessed for its antiapoptotic effects in human gastric adenocarcinoma (AGS) cells evidenced by acridine orange/ethidium bromide staining technique and Annexin-V assay. An i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…Our studies showed that upregulation of SOD2 maintains mitochondrial function, indicated by reduction in mitochondrial ATP production and MMP in SOD2 knockdown CRC cells. Such protection through maintaining mitochondrial integrity was previously reported in other cancer types 38 . Enhanced glycolysis is also a common characteristic in the majority of malignant tumors.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our studies showed that upregulation of SOD2 maintains mitochondrial function, indicated by reduction in mitochondrial ATP production and MMP in SOD2 knockdown CRC cells. Such protection through maintaining mitochondrial integrity was previously reported in other cancer types 38 . Enhanced glycolysis is also a common characteristic in the majority of malignant tumors.…”
Section: Discussionsupporting
confidence: 71%
“…Such protection through maintaining mitochondrial integrity was previously reported in other cancer types. 38 Enhanced glycolysis is also a common characteristic in the majority of malignant tumors. Our study provided a link between enhanced SOD2 expression and increased glycolytic activity.…”
Section: Regulation Of Energy Metabolism In Crcmentioning
confidence: 99%
“…Although ginger used as a herbal medicine or seasoning has been shown consistent effects of promoting mitochondrial function (Misawa et al., ; Oh et al., ), studies suggested varying conclusions in the effects of its components including 6‐gingerol and 6‐shogaol on mitochondrial function. It was reported that 6‐gingerol attenuated oxidative damage on cell death of neurons (Lee, Park, Kim, & Jang, ), while it damaged the mitochondrial function resulting in cellular apoptosis in several other cell types (Mansingh, O J, Sali, & Vasanthi, ; Nigam, Bhui, Prasad, George, & Shukla, ; Yang et al., ). 6‐Shogaol was consistently reported to damage mitochondrial function of cells (Annamalai, Kathiresan, & Kannappan, ; Chen et al., ; Warin, Chen, Soroka, Zhu, & Sang, ).…”
Section: Discussionmentioning
confidence: 99%
“…6-Gingerol has been previously shown to inhibit tumor cell growth through downregulation of cell-cycle regulators CDK1, cyclin A, and cyclin B1 and by repressing cyclin D1 in colorectal cancer cells [24], by activating caspases 3 and 9 and modulating mitochondrial functions in human gastric cancer cells [11], by inhibiting protein expression of the cyclin family and mTOR pathway in human cervical adenocarcinoma cells [15], by decreasing cyclin A and CDK expression, and by altering MAPK and PI3K-AKT pathways in pancreatic cancer cells [12]. The previous research results have indicated that the AKT-GSK 3β pathway and cyclins may be the common mechanism of action of 6-gingerol in its antitumor activities.…”
Section: Discussionmentioning
confidence: 99%
“…6-Gingerol, 1-[4′-hydroxy-3′-methoxyphenyl]-5-hydroxy-3-decanone, is a major pharmacologically active ingredient of ginger [9,10]. Compared to 6-shogaol, 8-gingerol, and 10-gingerol (three other phytochemicals in ginger), 6-gingerol is reported to exert a wide array of biochemical and pharmacological actions, including antibacterial, anti-inflammatory, antioxidant, and antitumor capabilities [11][12][13][14][15][16]. Evidence has shown, for example, that 6-gingerol can induce cell-cycle G2-phase arrest and apoptosis by activating caspases 3 and 7 in oral and cervical tumor cells [17], stimulate autophagy via drug-DNA interaction and caspase-3-mediated apoptosis in HeLa cells [16], inhibit cell proliferation though mitogen-activated protein kinase (MAPK)activator protein 1 (AP-1) signaling in colon cancer [13], and suppress metastasis in breast cancer [18].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%